2021
DOI: 10.3390/nu13051586
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Interventions to Improve Sleep in Team-Sport Athletes: A Narrative Review

Abstract: Athletes often experience sleep disturbances and poor sleep as a consequence of extended travel, the timing of training and competition (i.e., early morning or evening), and muscle soreness. Nutrition plays a vital role in sports performance and recovery, and a variety of foods, beverages, and supplements purportedly have the capacity to improve sleep quality and quantity. Here, we review and discuss relevant studies regarding nutrition, foods, supplements, and beverages that may improve sleep quality and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 65 publications
(112 reference statements)
0
15
0
Order By: Relevance
“…A more comprehensive discussion on nutrition and travel may be found elsewhere [189,[193][194][195]. Although it is beyond the scope of this review to discuss micronutrients and supplements, the authors would like to acknowledge the role of cherries and other phytonutrients in the management of sleep and soreness in team sports [196,197]. From our experience, we have seen these micronutrients and supplements used by basketball teams, especially at the professional level, usually in juice extract form, but they are also incorporated into food menus and drink smoothies.…”
Section: Nutrition For Travelmentioning
confidence: 99%
See 1 more Smart Citation
“…A more comprehensive discussion on nutrition and travel may be found elsewhere [189,[193][194][195]. Although it is beyond the scope of this review to discuss micronutrients and supplements, the authors would like to acknowledge the role of cherries and other phytonutrients in the management of sleep and soreness in team sports [196,197]. From our experience, we have seen these micronutrients and supplements used by basketball teams, especially at the professional level, usually in juice extract form, but they are also incorporated into food menus and drink smoothies.…”
Section: Nutrition For Travelmentioning
confidence: 99%
“…From our experience, we have seen these micronutrients and supplements used by basketball teams, especially at the professional level, usually in juice extract form, but they are also incorporated into food menus and drink smoothies. The reader is referred to the following reviews for further inquiry [196][197][198].…”
Section: Nutrition For Travelmentioning
confidence: 99%
“…We recently read with great interest the recent paper by Gratwicke, M et al (2021), "Nutritional Interventions to Improve Sleep in Team-Sport Athletes: A Narrative Review", within the journal Nutrients [1]. We applaud the research team for attempting to highlight the interaction between chrononutrition and sleep.…”
mentioning
confidence: 99%
“…For this Special Issue, research leaders in sports nutrition were approached and invited to submit current reviews in their areas of expertise [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The topics are novel and wide-ranging, and include updates and insights on protein [ 11 , 12 ], dietary patterns and nutritional interventions to support sleep, older athletes, and sports performance [ 13 , 14 , 15 ], pre-exercise nutrition [ 16 ], supplementation with betaine, iron, and creatine [ 17 , 18 , 19 ], and sports nutrition research methodologies for body composition and muscle glycogen analysis [ 20 , 21 ]. A major emphasis in all of the papers was a focus on strengths and weaknesses for various sports nutrition strategies, and insights for future research.…”
mentioning
confidence: 99%
“…The systematic review and meta-analysis by Chapman et al [ 12 ] concluded that protein supplementation improves strength and muscle mass during intensive and long-term training. Nutritional interventions, such as supplementation with tart cherry juice, kiwifruit, 20–40 grams of protein rich in tryptophan, and glycine late in the day were recommended as useful sleep-enhancement strategies for athletes in the narrative review by Gratwicke et al [ 13 ]. Strasser et al [ 14 ] focused on nutritional guidelines for older adults, including adequate energy and protein intake for countering losses in bone and muscle mass.…”
mentioning
confidence: 99%